A Qualitative Inquiry of the Lived Experiences of Music Therapists Who Have Survived Cancer Who Are Working with Medical and Hospice Patients - Lee, Jin Hyung (Frontiers in Psychology, 2016)
Cancer is a debilitating illness that affects more than one in every three Americans at sometime in their life time regardless of their social, cultural, ethnic, religious, or economic status. A few studies in the psychotherapy literature have investigated the impact of cancer on the personal and professional lives of psychotherapists. However, such investigations are yet unknown in medical or music therapy literature. In this descriptive phenomenological study, the researcher interviewed five American music therapists who have survived cancer and also work with patients in medical hospitals or hospice settings. The purpose of this study was to fully describe their lived experience of surviving cancer and examine how the cancer experience affected their clinical work thereafter. The data was analyzed using an open coding method from grounded theory which identified four major themes: (a) personal significance; (b) relational significance; (c) musical significance and (d) professional significance. The descriptions provided by these participants of their cancer experience as patients, survivors, and cancer surviving therapists, have revealed various psychosocial and physical issues encountered, and numerous coping methods they employed, and poignantly explained how their clinical approach evolved and expanded due to the personal experience of cancer. Specific issues in relation to countertransference, self-disclosure, and ways of developing empathic approaches without having such personal experience were discussed in addition to suggestions for future research.